2014
DOI: 10.1016/j.nucmedbio.2013.11.006
|View full text |Cite
|
Sign up to set email alerts
|

A heterodimeric [RGD-Glu-[64Cu-NO2A]-6-Ahx-RM2] αvβ3/GRPr-targeting antagonist radiotracer for PET imaging of prostate tumors

Abstract: Introduction In the present study, we describe a 64Cu-radiolabeled heterodimeric peptide conjugate for dual αvβ3/GRPr (αvβ3 integrin/gastrin releasing peptide receptor) targeting of the form [RGD-Glu-[64Cu-NO2A]-6-Ahx-RM2] (RGD: the amino acid sequence [Arg-Gly-Asp], a nonregulatory peptide used for αvβ3 integrin receptor targeting; Glu: glutamic acid; NO2A: 1,4,7-triazacyclononane-1,4-diacetic acid; 6-Ahx: 6-amino hexanoic acid; and RM2: (D-Phe-Gln-Trp-Ala-Val-Gly-His-Sta-Leu-NH2), an antagonist analogue of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 41 publications
6
31
0
Order By: Relevance
“…26,27 However, the focus has gradually shifted from labeling agonists with SPECT isotopes 26,27 such as 99m Tc and 111 In to labeling antagonists with PET isotopes [17][18][19]28,29 including 68 Ga, 64 Cu and 18 F. The advantages of PET include higher sensitivity and resolution compared to SPECT which leads to improved image quality and the ability to detect smaller lesions. In terms of pharmacological properties, it has recently been demonstrated by Cescato et al 16 that radiolabeled GRPR antagonists were superior to agonists for in vivo imaging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26,27 However, the focus has gradually shifted from labeling agonists with SPECT isotopes 26,27 such as 99m Tc and 111 In to labeling antagonists with PET isotopes [17][18][19]28,29 including 68 Ga, 64 Cu and 18 F. The advantages of PET include higher sensitivity and resolution compared to SPECT which leads to improved image quality and the ability to detect smaller lesions. In terms of pharmacological properties, it has recently been demonstrated by Cescato et al 16 that radiolabeled GRPR antagonists were superior to agonists for in vivo imaging.…”
Section: Discussionmentioning
confidence: 99%
“…16 Among BBN antagonists, the potent RM26 (D-Phe-Gln-Trp-Ala-ValGly-His-Sta-Leu-NH 2 ) has been widely derivatized for radiolabeling with 64 Cu/ 68 Ga and 111 In for imaging GRPR-expressing prostate cancer with positron emission tomography (PET) and single photon emission computed tomography (SPECT), respectively. [17][18][19] Recent successful detection of GRPR-expressing prostate cancer in clinical studies using RM26 derivatives ( 68 Ga-BAY86-7548 20 and 64 Cu-CB-TE2A-AR06 21 ) further demonstrated the potential usefulness of radiolabeled GRPR antagonists for prostate cancer imaging.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous previous studies have reported that each of the BnRs internalize agonist ligands, whereas antagonists show no or only minimal internalization, and also agonists stimulate rapid internalization of the BnRs[1,53–57]. The recent finding that radiolabeled-somatostatin antagonists gave superior imaging results to radiolabeled-agonists[58], led to similar studies in BnRs, and recent studies with GRPR report a similar finding with radiolabeled-GRPR-antagonists[16•,56,57,5965]. In general tumor-localization in vivo in animal studies and a few human-studies (Table 1) using radiolabeled-ligands has proven to be a sensitive method to image BnR-positive tumors and these results will be discussed under the specific tumor types in the following sections.…”
Section: Imaging and Targeted-delivery Of Cytotoxic-agents To Neopmentioning
confidence: 94%
“…Heterodimeric ligands were developed for dual targeting of GRPR and NPY receptors in breast cancer (61). Arg-Gly-Asp-bombesin hybrid peptides were also developed for dual targeting of GRPR and integrin a v b 3 -aiming receptors on tumor cells and vasculature (62). We think that it would also be helpful to consider dual targeting of GRPR and NTSR 1 in prostate cancer.…”
Section: Multiple Targetingmentioning
confidence: 99%